The Role Of Delayed Laparoscopic Suction For Intra-abdominal Collection Or Abscess Post Appendectomy In Paediatric Patients: Case Series And Review Of Literature - Dayang Anita Abdul Aziz; Surita Said; Marjmin Osman; Felicia Lim; Mahmud Mohd Nor; Faizah Mohd Zaki; Zarina Abdul Latiff (OAE Publishing Inc., 2024)
Non-Indexed Publication